Segregation in a Cu bicrystal - Jafta, Charl Jeremy (University of the Free State, 2010)
A literature study showed that the rate of segregation to a Cu(110) surface is higher than to a Cu(111) surface. The difference is mainly due to a change in the vacancy formation energy which determines the diffusion coefficient. The diffusion coefficient is a very important factor during kinetic segregation and determines the flux of atoms to the surface. The experimental verification of the calculations is very difficult due to the high number of parameters involved during measurements. In this study, the segregation parameters for Sb in a Cu bi-crystal, with (111) and (110) surface orientations, were determined. A unique experimental setup and measuring procedure was used to determine the concentration of the segregant as a function of temperature. This setup ensures exactly the same experimental conditions for both orientations allowing the researcher to directly compare the segregation parameters. The Auger Electron Spectroscopy (AES) spectrometer, used to measure the Sb enrichment on the Cu bi-crystal surfaces, was specially modified for these measurements. The deflection plates in the primary e- gun were physically aligned, horizontally and vertically, relative to the laboratory frame of reference. A computer program was developed to control the deflection of the e- beam during the measurements. Because it was decided on diffusional doping of the crystal an annealing system was designed and built. The system is consistently successful in annealing specimens at high temperatures for long periods of time in non corrosive atmospheres. Because of concerns that the grain boundary can influence the segregation, a secondary study was done on the migration of grain boundaries in polycrystalline Cu specimens. These studies indicate the inhibition of grain boundary mobility with small additions of Sb. The concentration build up on both surface orientations was monitored while the crystal was heated linearly with time, at different rates. The experimental data were fitted using the Modified Darken Model. The extracted Sb segregation parameters, in the Cu(110) surface are m2.s-1, kJ.mol-1, kJ.mol-1 and kJ.mol-1, and in the Cu(111) surface are m2.s-1, kJ.mol-1, kJ.mol-1 and kJ.mol-1. With the experimental conditions kept constant for both surface orientations, it is seen that there is a definite change in the pre-exponential factor and activation energy which compares well with values in literature. The different pre-exponential factors allows the opportunity to calculate, for the first time, the difference in the change in entropy ( ) for the two surface orientations as J.mol-1K-1. A unique custom build annealing system and experimental method used in this study proved to be highly successful and a change in the Sb segregation parameters, as a function of surface orientation, were experimentally verified.
Dissertation (M.Sc. (Physics))--University of the Free State, 2010
Keywords: Auger electron spectroscopy; Segregation (Metallurgy); Surfaces (Physics); Copper; Copper -- Surfaces; X-Ray diffractometer; SEM - Secondary Electron Microscopy; XRD - X-ray Diffraction; XPS - X-ray Photo-electron Spectroscopy; Grain boundary; AES modification; Amealing system; Bi - Bismuth; Sb - Antimony; (110) surface orientation; (111) surface orientation; Cu (Copper) bi-crystal